HUBUNGAN ANTARA USIA, JENIS KELAMIN, MASA KERJA DAN SIKAP TERHADAP SISTEM KERJA HYBRID DENGAN PRODUKTIVITAS KERJA KARYAWAN - Kurniasari, Kurniasari; Ibrahim, Rika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
The Covid-19 pandemic that has hit the world has had a major impact on Indonesia. One of them is the implementation of a hybrid work system that combines remote work and physical presence in order to achieve optimal employee work productivity. The attitude of employees to the work system can affect work productivity. The purpose of this study was to analyze the relationship between age, gender, length of service, and attitudes towards the hybrid work system with employee work productivity. This research is an analytical observational study with a cross-sectional approach. A total of 66 employees were selected as research projects using consecutive non-random sampling techniques. A valid questionnaire of attitudes towards hybrid work systems and work productivity is used to assess attitudes towards hybrid work systems and employee work productivity. The chi-square test with a meaningfulness level of 0.05 was used to assess the relationship between the two variables. The results of this study showed a relationship between age (p = 0.002), length of service (p = 0.001), and attitudes towards the hybrid work system with employee work productivity (p = 0.003). Gender is not related to work productivity (p=0.587). The implementation of a hybrid work system during a pandemic can be a good alternative to maintain high work productivity in employees.